Assessing Service Quality and Developing Improvement Strategies in Fire and Rescue Services - Oktovianus G. Pooroe; Montgomery Warbal; Selvia F. G. Renyut (Univiversitas Dr. Djar Wattiheluw, 2026)
Fire disasters remain a major public safety concern in Indonesia, with more than 10,000 incidents recorded annually during 2020–2024. This study examines the quality of fire management services provided by the Ambon City Fire and Rescue Service, identifies factors influencing service performance, and proposes strategies for improvement. A qualitative approach was employed through interviews, observations, and document analysis. The findings reveal that service quality has not fully met community expectations due to inadequate facilities and infrastructure, limited human resource capacity, underutilized information technology, weak inter-agency coordination, and low public awareness of fire prevention. To address these challenges, the study recommends an integrated strategy encompassing human resource development, infrastructure modernization, digital technology utilization, strengthened regulations and coordination, and community empowerment. These measures are expected to enhance service quality, improve emergency response effectiveness, and strengthen public safety in Ambon City.